Treatment of cryotherapy and orthotopic transplantation following chondromyxoid fibroma of zygomatic bone: A case report. Issue 31 (August 2018) - Zhu, Zhi-Chao; Yang, Yi-Fei; Yang, Xu; Liu, Yan; Cheng, Yi-nan; Sun, Zhao-Yao; Xu, Tian-Shu; Yang, Wen-Jun
Abstract: Introduction: Chondromyxoid fibrotherma (CMF) is a rare benign cartilage tumor that occurs more frequently in young males at the age of 20 to 30. It occurs more frequently on long bones, but rarely involves craniofacial bones. Case presentation: This study mainly introduced a 30-year-old male with CMF of zygomatic bone. Single tumor excochleation was conducted initially. However, CMF reoccurred, and then the following steps were adopted: firstly, the tumor was extensively excised; secondly, in vitro tumor excochleation was conducted; thirdly, the excised tumor bone was placed in liquid nitrogen for 3 cycles of cryoablation; finally, the orthotopic transplantation was performed to reconstruct the zygomatic appearance, with satisfactory follow-up efficacy obtained. Conclusions: Orthotopic transplantation after tumorectomy and cryopreservation of tumor bone in liquid nitrogen could lead to excellent therapeutic efficacy and deserves to be widely applied in clinical practice in the treatment of a male patient with CMF of zygomatic bone, because it not only radically eliminates the tumor and kills tumor cells, but also provides bony skeleton for the growth of new bone, thus greatly promoting postoperative aesthetic degree and reducing the occurrence rates of complications.